Analisis Tipe Kepemimpinan Paternalistik Dalam Peningkatan Pelayanan Publik di Tengah Situasi Pandemik Covid-19 - Siti Marwiyah; Nur Halima; Finni Maulidi (Universitas Islam Malang, 2020)
Currently, the Covid-19 pandemics have begun to cause real loss among the public. Many victims who have attacked Indonesian society, began to the sick even to death. It is enough to make the community panic and fear the Covid-19 pandemics. So how can a leader make people calm and take care. The handling done to date is social distancing. However, various forms of public service are still run by government. As a leader with the type of the head of the community that is widely found in the environment, it is still traditional. In other words, his legitimacy of leadership is seen as natural and normal with its organizational implications, such as commanding authority and decision making without having to consult with his subordinates in prioritizing togetherness. Research was conducted to know how the type of paternalistic leadership in the village of Ketapang Kota Probolinggo increased the public service in the middle of the Covid-19 pandemics. With the results of the paternalistic leadership type research affects the level of public servants in the Covid-19 pandemic.